La importancia de la auditoría forense preventiva para fortalecer el control interno en las cuentas por cobrar en las empresas del sector comercial de Palmira. (2021)
The purpose of this work is to analyze from the forensic audit and taking tool internal control as a mechanism to evaluate the management of accounts by charge and the financial impact in the business context of the city of Palmira.